A Systematic Review of the Complex Effects of Cannabinoids on Cerebral and Peripheral Circulation in Animal Models - Richter, J. Sebastian; Quenardelle, Véronique; Rouyer, Olivier; Raul, Jean Sébastien; Beaujeux, Rémy; Gény, Bernard; Wolff, Valérie (Frontiers in Physiology, 2018)
While cannabis is perceived as a relatively safe drug by the public, accumulating clinical data suggest detrimental cardiovascular effects of cannabinoids. Cannabis has been legalised in several countries and jurisdictions recently. Experimental studies specifically targeting cannabinoids' effects on the cerebral vasculature are rare. There is evidence for transient vasoconstrictive effects of cannabinoids in the peripheral and cerebral vasculature in a complex interplay of vasodilation and vasoconstriction. Vasoreactivity to cannabinoids is dependent on the specific molecules, their metabolites and dose, baseline vascular tone and vessel characteristics as well as experimental conditions and animal species. We systematically review the currently available literature of experimental results in in vivo and in vitro animal studies, examining cannabinoids' effects on circulation and reactive vasodilation or vasoconstriction, with a particular focus on the cerebral vascular bed.